Edukasi Terapi Butterfly Hug untuk Menurunkan Masalah Psikososial: Ansietas pada Masyarakat di Wilayah Kerja Puskesmas Tamalanrea Jaya Kota Makassar - Akbar Harisa; Suci Ahliyatul Muhinra; Andi Zafirah Fitri; Miftahul Hidayah; Rezky Awalya Ramadhani NB; Nur Hikmah D; Bulkis Rosyidi; Yodang Yodang (Jurnal Abdimas Kesehatan (JAK), 2023)
Anxiety is a condition that needs attention. Excessive worry about activities or events that take place almost every day, for 6 months or more is a frequent psychosocial problem, generally in adolescence to adulthood. Anxiety can be caused by various internal and external factors such as family history, history of trauma. Some people do not know how to deal with the anxiety they experience. For this reason, we from Hasanuddin University Nurse Profession Students, are trying to hold counseling regarding how to deal with anxiety with butterfly hug therapy in the work area of the Tamalanrea Jaya Makassar Health Center. This activity aims to increase public knowledge in dealing with anxiety experienced. The method used is a demonstration using leaflets and banners as reading material that can add to the public's insight regarding anxiety and butterfly hug relaxation technique. The results achieved from this counseling activity are that the community understands, understands, and can explain correctly related to psychosocial problems, namely anxiety and how to handle them with the butterfly hug relaxation technique